Ranking factors for supplier’s selection by TOPSIS method - Puška, Adis (Oeconomica Jadertina, 2017)
Supplier’s selection is a first step in the supply chain. Supply chain except supplier’s selection includes many other activities. However, with the proper suppliers selection can be realized other objectives too within the supply chain.When selecting new suppliers each company puts specific criteria that need to fulfill and on the basis these criteria i.e. factors make the decision. Depending on which industry belongs to the company, they use a variety of factors in choosing new suppliers. These factors are diverse. This paper, unlike other papers explores the difference they make individual factors for the supplier’s selection using the expert opinion. For experts used in this study were taken from those who have published scientific papers on this topic. In this way it will be ranked factors for the new supplier’s selection using TOPIS methods of multi-criteria analysis and through expert opinions. Using this approach it will be determined what are the most important factors for new supplier’s selection.
Keywords: The factors for selecting new suppliers; Supplier’s selection; TOPSIS method; ranking; expert opinion